Comparison of Sexual Functions in Pregnant and Non-Pregnant Women - Aydin, Mustafa; Cayonu, Neval; Kadihasanoglu, Mustafa; Irkilata, Lokman; Atilla, Mustafa Kemal; Kendirci, Muammer (Urology Journal, 2015)
Purpose: The physiology and anatomy of pregnant women change during pregnancy. Pregnancy is an anatomically and physiologically amended process experienced by women and as a result of these changes, sexual life of pregnant women alters during pregnancy. We aimed to compare sexual functions of pregnant and non-pregnant women. Materials and Methods: Sexually active 246 pregnant women were included into this cross-sectional controlled study. A total of 210 non-pregnant women were served as control. Both groups were compared in terms of age, gestational age, presence of urinary incontinence, body mass index, and obstetrical history. Sexual functions of the women were evaluated with Female Sexual Function Index (FSFI). Data were analyzed using chi-square, Mann-Whitney U, Fisher's Exact, Shapiro Wilk, Kruskal Wallis and Dunnett's tests where appropriate. The P values < .05 were considered statistically significant. Results: Mean age in both groups were comparable (P = .053). Median total FSFI scores in the pregnant women were significantly lower than those non-pregnant (18.9 vs. 22.7; P < .05). Additionally, the subgroup analyses of the FSFI scores were found that, total FSFI score is significantly lower in the pregnant group compared to non-pregnant group (P < .05). Furthermore, rate of sexual dysfunction in pregnant women was significantly higher than those non-pregnant women (91.08% vs. 67.61%, P = .0001). However, in pregnant women, no meaningful difference in rate of sexual dysfunction was found according to the trimesters (P = .632). Moreover, gravidity and parity exhibited negative impacts on the sexual functions. But number of abortions did not affect sexual function. Conclusion: These data demonstrate that pregnancy significantly diminishes sexual function in women. We believe that, couples need to be counseled regarding the impact of pregnancy on sexual functions.